Germanium-based technologies from materials to devices - Claeys, Cor L.; Simoen, E.; Simoen, Eddy (Elsevier, 2007)
Germanium is a semiconductor material that formed the basis for the development of transistor technology. Although the breakthrough of planar technology and integrated circuits put silicon in the foreground, in recent years there has been a renewed interest in germanium, which has been triggered by its strong potential for deep submicron (sub 45 nm) technologies. Germanium-Based technologies: From Materials to Devices is the first book to provide a broad, in-depth coverage of the field, including recent advances in Ge-technology and the fundamentals in material science, device physics and semiconductor processing. The contributing authors are international experts with a world-wide recognition and involved in the leading research in the field. The book also covers applications and the use of Ge for optoelectronics, detectors and solar cells. An ideal reference work for students and scientists working in the field of physics of semiconductor devices and materials, as well as for engineers in research centres and industry. Both the newcomer and the expert should benefit from this unique book. * State-of-the-art information available for the first time as an all-in-source * Extensive reference list making it an indispensable reference book * Broad coverage from fundamental aspects up to industrial applications.